2019
DOI: 10.1007/s10103-019-02896-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozone and diode laser (635 nm) in reducing orthodontic pain in the maxillary arch—a randomized clinical controlled trial

Abstract: The effect of ozone, diode laser irradiation, and presence of teeth crowding/spacing on pain perception in orthodontic patient was tested. Overall, 76 patients [55 women and 21 men; age 35.1(6.4) years] who met the inclusion criteria participated in the study. Immediately after fixed orthodontic appliance placement, the patients were exposed to a pain relief treatment (one single session) using either 635-nm diode laser (SmartM, Lasotronix, Warsaw, Poland) or ozone therapy (OzoneDTA, Apoza, New Taipei City, Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
1
27
0
1
Order By: Relevance
“…However, in the split-mouth clinical study presented by AlSayed et al, the authors obtained no difference in relieving elastomeric separators induced orthodontic pain after LLLT, applied at two different laser energy values (4 and 16 J). However, there is some bias in pain analysis in this study because the pain feeling by the patients could alsom be caused by the fixed orthodontic appliance [24]. There is no consistent thesis on pain during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, in the split-mouth clinical study presented by AlSayed et al, the authors obtained no difference in relieving elastomeric separators induced orthodontic pain after LLLT, applied at two different laser energy values (4 and 16 J). However, there is some bias in pain analysis in this study because the pain feeling by the patients could alsom be caused by the fixed orthodontic appliance [24]. There is no consistent thesis on pain during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 78%
“…The PBM is a minimal-invasive treatment allowing to stimulate cellular processes such as ATP, DNA, and RNA synthesis [16,22]. Many authors demonstrated the positive effect of LLLT in bone healing [22], osteoblasts [22], fibroblasts [13] proliferation, nerve repair [19], increased peri-implant bone density [23], and reduced pain in orthodontics [24]. Our study aimed at testing the photomodulation effect of the LLLT on implant stability of orthodontic mini-implants placed in a maxilla and mini-implants failure rate and a pain level after the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diode lasers in periodontology can also be used for gingivectomy/gingivoplasty of hypertrophic gingiva. A high relief of pain was also confirmed in orthodontic treatmen of patients after application of a diode laser with wavelength 635 nm [34]. Photobiomodulation (PBM) is especially indicated in the treatment of patients at risk of bacteremia or with immune deficiency [28].…”
Section: Antimicrobial Photodynamic Therapymentioning
confidence: 89%
“…18,21,22 . Other modalities including, photo biomodulation, low level laser therapy, vibration were noted to have a substantial level of pain reduction [23][24][25][26][27] . In the present study pain was tolerable for all the patients hence no other therapy was advised to reduce pain.…”
Section: Discussionmentioning
confidence: 99%